The implementation of BIM in construction projects - Sinenko, Sergey; Hanitsch, Pavel; Aliev, Sheroz; Volovik, Mikhail (E3S web of conferences, 2020)
Building Information Modeling Implementation (BIM) is a management task that has undergone major changes. Therefore, identifying the critical success factors in BIM implementation and identifying its implementation challenges in the construction industry is a prerequisite for this change process. The purpose of this research is to understand the construction industry in order to provide a clear understanding of the application of BIM and to provide a suitable way of the mobility of people to implement more comprehensive BIM, which in turn, implements modeling. Building information provides strategies and recommendations for the construction industry. This research, based on a review of previous study, BIM implementation methods and critical success factors in the field of implementation have been discussed, which opens the way for quantitative and qualitative method analysis. Also provides a solid foundation for organizations to make informed decisions in implementing BIM in the body of the organization structure. The main purpose of this research is to identify the factors that are important for the success of BIM implementation. Such factors include BIM potentials and the impact of these potentials on improving the performance of the companies that implement BIM. The research based on a literature review, and presents survey results and significant factors identified on the impacts of BIM implementation and organizational performance improvement.